Ijarah Application in Shari’ah Mutual Funds - Suyoto Arief; Erika Rishan Adillah; Arizqiya Nurfattah (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
Investment is one way to increase income. The Islamic capital market is one of the instruments for investing that functions as a bridge between investors and entrepreneurs who need capital with the basis and principles of Shari'a. The Islamic Capital Market provides various products including Sharia mutual funds. The mechanism for implementing Shari'a Mutual Funds involves Investment Managers (MI) who represent all investors and Custodian Banks as banks that maintain, maintain, and guarantee the security of investors' money. With so many parties involved in mutual funds, it is possible that the contracts used are various. The purpose of this study is to identify the application of ijarah in sharia mutual funds. This research uses qualitative calculations. Data sourced from the Quran, al-Hadith, opinions of scholars and economists, journals both printed and online materials. The results of this study illustrate that the application of ijarah in Sharia mutual funds is found in the provision of wages/rewards (ujroh) to Custodian Banks for services in investment administration, securities storage and investment funds from Mutual Funds taken from net asset value (NAV) calculated in percentages. However, there are still irregularities, in which wages (ujroh) are calculated in percentage terms. The determination of wages should be calculated by nominal not by percentage, because it includes the form of gharar that is forbidden in sharia.